Protecting group-free photocatalyzed O-arylation of quinic acid - Miguel A. Bárbara; Nuno R. Candeias; Luis F. Veiros; Filipe Menezes; Andrea Gualandi; Pier G. Cozzi; Carlos A.M. Afonso (Tetrahedron Green Chem)
This study presents a novel and environmentally friendly approach to the preparation of quinic acid-derived esters from photocatalyzed O-arylation with haloarenes. This study expands the quinic acid-derived chemical space from renewable biomass by harnessing the power of visible-light-driven photocatalysis under mild conditions without the need for protecting groups. A thorough screening of reaction conditions, including the choice of photocatalyst, solvent, base, nickel source, and ligand, led to the identification of the most effective conditions, these being 5CzBN as the optimal photocatalyst, and glyme-based nickel complexes as the preferred nickel source. These conditions enabled the formation of O-arylated products with good yields without noticeable formation of decarboxylated products. Computational calculations support the proposed mechanism for the O-arylation process, based on oxidative addition, anion exchange, and reductive elimination upon energy transfer from the photocatalyst to the Ni(II) species. Computational considerations for a nickel-catalyzed photodecarboxylative arylation mechanism suggest that the oxidation of quinate by the excited photocatalyst or other species derived thereof is considerably less favorable than a pathway only involving energy transfer to a nickel species. The research provides valuable insights into the mechanism of this environmentally conscious transformation.